Relationship between Customer Satisfaction and Business Performance: A Case Study of Lloyds Bank UK - Neupane, Ramesh (International Journal of Social Sciences and Management, 2014)
Purpose:The main purpose of this research is to examine the relationship between customer satisfaction and business performance on a case of Lloyds Bank UK. Moreover, it also evaluates the customer satisfaction level and examines the business performance of Lloyds Bank through examining various factors of business performance. Design/Methodology: The necessary data were collected through structured questionnaires from five branches of Lloyds Bank. The sample of 250 customers and 80 management level employees are used in this research. The collected data were analysed through correlation and regression analysis, mean and standard deviation through SPSS 20. Main Findings: The mean score of every variable is more than 3 out of 5 and mean score of overall customer satisfaction is 3.89 (77.8% satisfaction) indicates that there is high level of customer satisfaction in Lloyds Bank. Similarly, mean score of overall business performance is 3.73 (75%) shows a high level of business performance. The Pearson’s coefficient of correlation between overall customer satisfaction and business performance is r = 0.343 indicated that they are positively correlated. But, regression analysis shows that customer satisfaction has not significant effect on business performance as P = 0.139 and β = 0.343. Thus, it shows that customer satisfaction has week positive relationship with business performance. Value: This research refines and reinforces the body of knowledge and understanding regarding to customer satisfaction and organisational performance analysis. These findings may be useful to the organisation for future planning to enhance customer satisfaction to increase business performance. The instruments may have practical implications for examining customer satisfaction and business performance in any business organisations. Limitations: This research was conducted through cross sectional approach and limited sample of 250 customers and 80 employees from 16 branches in the main cities of the UK. So, the findings are limited to a bank in the main cities. DOI: http://dx.doi.org/10.3126/ijssm.v1i2.10019 Int. J. Soc. Sci. Manage. Vol-1, issue-2: 74-85